1971
DOI: 10.1128/aem.22.5.909-913.1971
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated Eastern Equine Encephalomyelitis Vaccines Prepared in Monolayer and Concentrated Suspension Chick Embryo Cultures

Abstract: Eastern equine encephalomyelitis vaccines were prepared with virus propagated in stationary monolayer cultures and in concentrated suspension cultures of primary chick embryo cells. Virus pools for vaccine preparation were inactivated by three different methods: 0.05% formalin, 41 C heat, and 0.16% ,3-propiolactone. Heat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Formalin-inactivated WEEV, EEEV, and VEEV vaccines are weakly immunogenic, possibly because of cross-linking of proteins and masking of important immune epitopes required for protection. These are being used for at-risk laboratory workers under Investigational New Drug status (7,28,(34)(35)(36)(37). Another modality, a trivalent EEV replicon vaccine, failed to seroconvert all animals and protect completely against each aerosol EEV challenge in NHPs (13).…”
Section: Discussionmentioning
confidence: 99%
“…Formalin-inactivated WEEV, EEEV, and VEEV vaccines are weakly immunogenic, possibly because of cross-linking of proteins and masking of important immune epitopes required for protection. These are being used for at-risk laboratory workers under Investigational New Drug status (7,28,(34)(35)(36)(37). Another modality, a trivalent EEV replicon vaccine, failed to seroconvert all animals and protect completely against each aerosol EEV challenge in NHPs (13).…”
Section: Discussionmentioning
confidence: 99%
“…We inactivated at 37 C with the vessels kept in constant motion throughout the periods employed. Other investigators have shown that temperature is critical and that lower temperatures greatly decrease the rate of inactivation (7,16,18). In future studies, selected lots of inactivated Trinidad VEE vaccine will be tested in Equidae to establish parameters for volume and number of doses required, interval between doses, persistence of immunity, and effectiveness as a "booster" in equines previously immunized with attenuated VEE vaccine as well as in offspring of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Also, lots of virus were propagated in concentrated CE suspension cultures by the methods reported for Eastern equine virus (White et al, Arch. Gesamte Virusforch., 36: [13][14][15][16][17]1972).…”
Section: Methodsmentioning
confidence: 99%
“…Vaccine preparation and potency assays. The vaccines from virus grown in MK monolayers and concentrated CE suspension cultures were prepared as previously described (2,13). Potency assays of the vaccines were performed in 3-to 4-week-old Swiss Bagg strain male mice which were obtained from the Department of Laboratory Animals, Walter Reed Army Institute of Research, Washington, D.C.…”
Section: Methodsmentioning
confidence: 99%